Biomedical signal processing and applications - Ibrahimy, Muhammad Ibn (2010)
In biomedical signal processing, the aim is to extract clinically, biochemically or pharmaceutically relevant information in order to enable an improved medical diagnosis. All living things, from cells to organism, deliver signals of biological origin. Such signals can be electric, mechanical, or chemical. All such signals can be of interest for diagnosis, for patient monitoring and biomedical research. The main task of processing biomedical signals is to filter the signal of interest out of from the noisy background and to reduce the redundant data stream to only a few,but relevant parameters. This paper will cover biomedical signal processing as used in diagnostic instrumentation. A number of current research projects will also be outlined with emphasis on intelligent medical diagnosis system.